Utility of cochlear perilymph biomarkers for hearing loss - A systematic review - Kujani Wanniarachchi; Sita Tarini Clark; Neil Donnelly; Manohar Bance; Nathan Creber (PLoS ONE, 2025)
The live cochlea is a critical and delicate sensory organ with tissue sampling posing a risk to balance and hearing functions. Consequently, a researchers’ ability to investigate the pathogenesis of sensorineural hearing loss (SNHL) has been limited, commonly involving in vitro models, translational animal models and post-mortem analysis. Previous human studies investigating SNHL have primarily been restricted to using peripheral blood or cerebrospinal fluid samples that indirectly measure inner ear pathologies. More recently, the establishment of a novel, safe, and feasible technique for intraoperative perilymph sampling has enabled the collection of a ‘liquid biopsy’ of the cochlea whilst still preserving inner ear function. This crucial development has opened avenues for characterising the cochlea microenvironment and subsequently investigating the mechanisms of SNHL. Perilymph sampling may also provide insights into why postoperative outcomes vary between cochlear implant users with otherwise similar preoperative clinical characteristics. The present systematic review aimed to elucidate the gap in the literature regarding the utility of perilymph biomarkers in SNHL diagnosis, treatment, and prognosis. Medline, Embase, Web of Science, and Scopus were searched for two groups of keywords related to ‘biomarker’ and ‘SNHL’. Of the 7471 studies initially identified, 15 met the inclusion criteria. Based on the findings of these studies, biomarkers were grouped into six main categories based on their underlying pathological processes: heat shock proteins (HSP), immune-related, microRNA, neurotrophic, metabolome, and structural. For each category, this review identifies potential biomarkers that should be carefully validated in future studies. In particular, HSP70 and HSP90, complement components, mi1299, mi1270, and brain-derived neurotrophic factor regulated proteins may help direct future studies focused on characterising the biomarker profile in patients with SNHL. Future studies should ideally also utilise larger cohorts of patients with specified hearing loss aetiologies. Such studies may help to pave the way towards a more accurate diagnosis of SNHL, improved prediction of cochlear implantation prognosis, and targeted therapeutic management.